Explaining the socio-economic inequalities in child immunisation coverage in Zimbabwe - Chigwenah, Tariro (University of Cape Town, 2021)
Socioeconomic inequalities in health have received significant attention globally because of the well-known association between wealth and health. A lot of studies show that poor people are more prone to sickness than their counterparts. Immunisation has been a key antidote to avert deaths for children under the age of 5. This study represents an initial attempt to assess specific variables that contribute to socioeconomic inequalities in immunisation coverage in Zimbabwe. Data were obtained from the 2015 Zimbabwe Demographic Health Survey, a nationally representative survey. Immunisation coverage was measured using four categories: full immunisation (a child who will have received 10 doses of vaccines), partial immunisation (a child who will have received at least one but not all vaccines), no immunisation (a child who will not have received any immunisation dose from birth) and immunisation intensity (a proportion of doses received to total doses that they should have received). Inequalities in immunisation coverage in Zimbabwe were assessed using concentration curves and indices. A positive (negative) concentration index indicates immunisation coverage concentrated among the rich (poor). The concentration index was decomposed to identify how different variables contribute to the socioeconomic inequality in immunisation coverage in Zimbabwe. Results indicate that immunisation intensity and full immunisation concentration indices were (0.0154) and (0.0250) respectively, indicating that children from lower socio-economic status are less likely to receive all doses of vaccines. No immunisation and partial immunisation concentration indices were (-0.0778) and (-0.0878) indicating that children from higher socioeconomic status are more likely to have their children immunised opposed to their poor counterparts. The main contributors to socioeconomic inequality in immunisation coverage are the mother's education, socioeconomic status and place of residence (rural/urban and province). While immunisation services are free of charge in the public health sector in Zimbabwe, coverage rates are higher among the wealthy, which shows that there may be barriers to utilising these services that may not be the direct cost of vaccination. There have to be measures by the government to reach people in areas that are not easily accessible. Also, more needs to be done to reduce socioeconomic inequalities in Zimbabwe.